Upaya Kepala Sekolah dalam Menertibkan Administrasi Pembelajaran Bagi Guru di SD IT Quran Darul Ikhlas Al-Islami Tambang Baru Kabupaten Merangin - Melly Nispiarlen; Apdoludin; Megawati (Yayasan Al-Afif, 2026)
This study was motivated by the incomplete learning administration of several teachers at SD IT Quran Darul Ikhlas Al-Islami Tambang Baru, Merangin Regency. Learning administration is an important part of teacher professionalism because it supports the planning, implementation, and evaluation of instruction. This study aimed to describe the principal’s efforts to improve teachers’ learning administration and to identify supporting and inhibiting factors. A qualitative case-study approach was employed from 1 to 13 September 2025. The principal served as the main informant, while four homeroom teachers from Grades I, II, IV, and VI served as supporting informants. Data were collected through non-participant observation, semi-structured interviews, and documentation. Data credibility was examined through source and method triangulation, and the data were analyzed through reduction, display, conclusion drawing, and verification. The findings show that the principal’s efforts included classroom supervision, participation in training and workshops, learning communities and teacher working groups (KKG), and motivational seminars. A formal reward-and-consequence policy had not yet been established, although praise and individual coaching were practiced. Supporting factors included the principal’s competence, adequate facilities, and teachers’ motivation and awareness. Inhibiting factors included limited time and workload, fluctuating motivation, and limited understanding of the Merdeka Curriculum. Overall, the principal’s efforts contributed to more orderly learning administration, but continuous monitoring, intensive mentoring, and optimal use of digital technology are still needed.